2021
DOI: 10.1111/ijcp.14734
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal symptoms and related factors in postacute COVID‐19 patients

Abstract: Aim There is a lack of an overview of the factors associated with postacute COVID‐19 musculoskeletal symptoms. The aims of this study were as follows: 1‐ to evaluate the most frequent admission symptoms and the frequency of musculoskeletal symptoms in postacute COVID‐19 patients; and 2‐ to determine the related factors with the postacute COVID‐19 musculoskeletal symptoms. Methods A total of 280 postacute COVID‐19 patients (183 females, 97 males) were enrolled and divide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
72
6
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(92 citation statements)
references
References 22 publications
8
72
6
6
Order By: Relevance
“…19 Differences in age, sex, preexisting comorbidities—particularly history of musculoskeletal pain (data not considered in most studies)—or severity of the disease could explain discrepancies. On the contrary, our results fall slightly below from those reported by 3 small cohort studies providing prevalence rates of musculoskeletal post-COVID pain up to 60% after 1 7,27 and 3 44 months. Only one study considered the presence of previous musculoskeletal pain.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…19 Differences in age, sex, preexisting comorbidities—particularly history of musculoskeletal pain (data not considered in most studies)—or severity of the disease could explain discrepancies. On the contrary, our results fall slightly below from those reported by 3 small cohort studies providing prevalence rates of musculoskeletal post-COVID pain up to 60% after 1 7,27 and 3 44 months. Only one study considered the presence of previous musculoskeletal pain.…”
Section: Discussioncontrasting
confidence: 99%
“…Finally, we also observed that a longer hospital stay was a risk factor, but showing a smaller influence, for musculoskeletal post-COVID pain, in agreement with a previous study. 7 It is possible that hospitalization factors such as physical inactivity or treatment received for managing the infection could promote future musculoskeletal post-COVID pain.…”
Section: Risk Factorsmentioning
confidence: 99%
“…Musculoskeletal pain (myalgia) is one of the most common symptoms experienced during the acute phase of severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) infection [ 1 , 2 ]. In addition, pain is also present in up to 18% of individuals experiencing post-COVID symptoms during the first year after infection [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Even after 3 months of a healed COVID-19 illness, many patients still experience persistent symptoms with a heterogeneous pattern consisting mainly of respiratory and neuropsychological complaints. Still, otolaryngological, endocrinological and dermatological symptoms are frequently reported 1 3 . The most common symptoms are dyspnoea and fatigue (“head fog”).…”
Section: Introductionmentioning
confidence: 99%